Analisis Literasi Teknologi Informasi dan Komunikasi dalam Pembelajaran Jarak Jauh di Masa Pandemi - Rustan Efendy; Siti Ahsanul Haq (IAIN PAREPARE, 2022)
This research was motivated by a change in the learning process that was initially carried out face-to-face and turned into online learning. The purpose of this study was to determine the importance of literacy regarding information and communication technology in teaching and learning. This type of research is literature review research by utilizing reference sources related to the discussion. The results of this literature review show that it is important for educators and students to have and understand basic information and communication technology literacy in learning that has the courage to make an impact during the learning process and achieve the goals to be achieved